Use of Epothilone B (Patupilone) in Refractory Lymphoma and Advanced Solid Tumors in Dogs. (3rd December 2012) - Meier, V.; Geigy, C.; Grosse, N.; McSheehy, P.; Rohrer Bley, C.
Abstract : Background: The epothilones are microtubule‐stabilizing agents with promising antitumor effect in refractory and metastatic tumors in humans. The toxicity profile is considered more favorable than in taxanes. The safety of epothilone B (patupilone) has not been evaluated in tumor‐bearing dogs. Objectives: To evaluate the inhibition of proliferation in canine tumor cells after patupilone treatment. To assess toxicity profile and maximally tolerated dose of patupilone in dogs with refractory tumors. Animals: Twenty client‐owned dogs with various malignancies. Methods: Prospective clinical study. The inhibition of proliferation was assessed with a proliferation assay in vitro in canine hemangiosarcoma and lymphoma cell lines. Dogs received patupilone IV once a week for 2 treatments (= 1 treatment cycle). Dose was escalated with 3 dogs per cohort and 20% increments. Adverse effects were graded accor‐ding to the VCOG‐CTCAE v1.0. Results: Both canine cell lines were sensitive to patupilone with approximately 50% decrease in proliferative activity at 0.2–1 nM. In vivo, dose‐limiting adverse effects occurred at 3.3 mg/m 2 ; main adverse effects were diarrhea, anorexia, vomiting, and nausea. Neither neutropenia nor peripheral neuropathy was observed. Maximally tolerated dose for 2 patupilone administrations once weekly IV is 2.76 mg/m 2 . Three per 11 dogs receiving more than 1 treatment cycle showed partial remission in the short period of observation. Conclusions and Clinical Importance: Canine tumor cells show inhibition of proliferation to patupilone in vitro. Clinically, a dose of 2.76 mg/m 2 IV is well tolerated in dogs with spontaneously occurring tumors.